Organocatalytic cascade knoevenagel-michael addition reactions: direct synthesis of polysubstituted 2-amino-4H-chromene derivatives - Jadhav, Sanjay N.; Patil, Seema P.; Sahoo, Dipti Prava; Rath, Dharitri; Parida, Kulamani; Rode, Chandrashekhar V. (Catalysis Letters, 2020)
In this report, we documented novel strategy for the synthesis of bioactive polysubstituted 2-amino-4H-chromine derivatives under a heterogeneous Al-MCM-41-LDH@APTES (ALAM) catalysis. A synthetic procedure is developed to prepare Al-MCM-41-LDH@APTES (ALAM) heterogeneous basic catalysts. Mesoporous Al-MCM-41 is functionalized by known grafting chemistry via layered double hydroxide (LDH) nanosheets and (3-aminopropyl)triethoxysilane (APTES) moiety as a basic organocatalyst. The resulting catalysts contain amino group functionality on the external surface as well as inside the layers and the basicity can be tuned by the loading of APTES. The samples were fully characterized by Si-29 and C-13 CP/MAS NMR, infrared absorption spectroscopy, TEM, XPS, EDX, TGA, XRD, CO2-TPD, N-2 adsorption isotherms measurements, and they were successfully examined for the cascade type Knoevenagel-Michael addition reactions. The product yields associated with these substrates were optimized, and key reaction parameters affecting the yields were identified. The present catalytic method is simple and robust for diversity oriented synthesis which proceeds good to excellent yields without generating any hazards waste. The broad substrate scope, excellent functional group compatibility makes this protocol highly useful towards synthesis of polysubstituted alpha-cyanoacrylates, alpha-cyanoacrylonitriles and 2-amino-4H-chromenes with an electron-donating or electron-withdrawing group. We have also successfully established a flow reaction system, gram-scale synthesis as well as catalyst recyclability up to six catalytic cycles without appreciable loss of its activity. Graphic
Keywords: 2-Amino-4H-chromines; Amine functionalized solid catalysts; cascade synthesis; Diversity oriented syntheses (DOS); flow chemistry